2019
DOI: 10.1038/s41408-019-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Calr mutations homologous to human CALR mutations only exhibit mild thrombocytosis

Abstract: Calreticulin ( CALR ) exon 9 frameshift mutations, commonly detected in essential thrombocythemia (ET) and primary myelofibrosis patients, activate signal transducer and activator of transcription (STAT) proteins in the presence of Myeloproliferative Leukemia Virus (MPL) and induce ET in vivo. Loss of the KDEL motif, an endoplasmic reticulum retention signal, and generation of many positively charged amino acids (AAs) in the mutated C-terminus are thought to be important for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Next, we selected a clone that had a homologous frameshift mutation to human mutation (19 base deletion) for mouse creation. Although a slight increase in platelet count was observed, megakaryocytes and hematopoietic stem/progenitor cells were not increased [45]. A group from Belgium also created a mouse model with a 61 or 52 base deletion at Calr gene exon 9 on the mouse genome using a similar method; however, the phenotype was limited to an extremely mild increase in platelets, similar to our results [46,47].…”
Section: Ki Modelsupporting
confidence: 86%
See 1 more Smart Citation
“…Next, we selected a clone that had a homologous frameshift mutation to human mutation (19 base deletion) for mouse creation. Although a slight increase in platelet count was observed, megakaryocytes and hematopoietic stem/progenitor cells were not increased [45]. A group from Belgium also created a mouse model with a 61 or 52 base deletion at Calr gene exon 9 on the mouse genome using a similar method; however, the phenotype was limited to an extremely mild increase in platelets, similar to our results [46,47].…”
Section: Ki Modelsupporting
confidence: 86%
“…A group from Belgium also created a mouse model with a 61 or 52 base deletion at Calr gene exon 9 on the mouse genome using a similar method; however, the phenotype was limited to an extremely mild increase in platelets, similar to our results [46,47]. The mouse CALR del19 mutant protein has a weaker binding ability to murine MPL than human CALR del52 protein [45]. This is why the human CALR del52 mutation can induce ET in mice, but the murine Calr del19 mutation cannot induce the full ET phenotype.…”
Section: Ki Modelsupporting
confidence: 78%
“…In a similar manner, Li J et al also showed a slight increase in WBC in heterozygous del52 KI mice, more reproducible and significantly higher in homozygous animals 13 . Similarly to heterozygous del52 KI mice, there was a moderate leukocytosis in the CRISPR-Cas9-mediated murine del52 KI mice 12 , while no change in WBC counts was seen in the human del52 TG and the CRISPR-Cas9-mediated murine del61 and murine del19 KI mice [10][11][12] . We show here that the increased WBC population in del52 and ins5 homozygous KI mice includes Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In the present work, we conducted a direct comparison of the effects of heterozygous and homozygous physiopathological expression of del52 and ins5 mutants on hematopoiesis using inducible conditional KI mice. We chose to express chimeric mouse/human proteins based on the fact that mutated C-terminal tails of the two species display different amino acid composition and we thus generated these del52 and ins5 KI mice before the recent demonstration that the human and murine mutated C-terminal tails have close oncogenic properties 11,14 . Expression of del52 induces a stronger phenotype including thrombocytosis, leukocytosis, megakaryocytic and progenitor amplification as well as a penetrant fibrosis in spleen compared to ins5.…”
mentioning
confidence: 99%
“…Several mutant Calr mice models have also been established, all exhibit an ET-like phenotype [80][81][82][83]. Myelofibrosis phenotype was observed only in the homozygous Calr mutant mice model [81].…”
Section: Calr Mutationmentioning
confidence: 99%